2018
DOI: 10.1148/radiol.2017162756
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation versus Hepatic Resection for Small Hepatocellular Carcinoma: Systematic Review of Randomized Controlled Trials with Meta-Analysis and Trial Sequential Analysis

Abstract: Purpose To compare the benefits and harms of radiofrequency ablation (RFA) and hepatic resection (HR) and to test the consistency of currently available evidence. Materials and Methods PubMed, Embase, and the Cochrane Library were systematically searched for randomized controlled trials (RCTs) that compared the effects of HR and RFA for Barcelona Clinic Liver Cancer very early or early stage hepatocellular carcinoma (HCC). The primary outcome was overall survival, and secondary outcomes were recurrence rate, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
161
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 44 publications
3
161
0
Order By: Relevance
“…Nonetheless, limited parenchyma resections do not significantly affect the oncologic prognosis or recurrence risk in the treatment of HCC . We should also acknowledge the increasing evidence on less invasive approaches (as thermal ablation) offering similar outcomes to resection for select patient populations with less incidence of complications and provide an alternative treatment strategy for patient management . These types of approaches need to be considered as part of a broader, multimodality strategy in the treatment and management of HCC patients especially in high risk patient as elderly ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, limited parenchyma resections do not significantly affect the oncologic prognosis or recurrence risk in the treatment of HCC . We should also acknowledge the increasing evidence on less invasive approaches (as thermal ablation) offering similar outcomes to resection for select patient populations with less incidence of complications and provide an alternative treatment strategy for patient management . These types of approaches need to be considered as part of a broader, multimodality strategy in the treatment and management of HCC patients especially in high risk patient as elderly ones.…”
Section: Discussionmentioning
confidence: 99%
“…Strong patient motivation for surgery and a lack of standardized risk assessment may expose patients to excessive risk of major post‐operative morbidity and mortality or poor long‐term prognosis. Conversely, failure to offer surgery with curative intent to patients who are judged unfit based on generic and imprecise risk variables is unacceptable …”
Section: Discussionmentioning
confidence: 99%
“…However, these data are not conclusive because of some methodology limitations. In fact, large retrospective series [101-104], propensity score analyses [105-112], one randomized trial [80], and 2 recent meta-analyses [94, 113] demonstrated superiority of surgery over RFA in terms of local disease control, even for 2–3 cm HCC. One multicentre Italian study collected 544 patients with single HCC ≤3 cm and compensated cirrhosis [104].…”
Section: Resultsmentioning
confidence: 99%
“…Short-term outcomes were improved by LLR and MWA, but disease-free survival was decreased in the local ablation group. In the meta-analysis conducted by Xu et al [113], RFA and resection had similar overall survival at 1 and 3 years, whereas RFA resulted in decreased overall survival compared with resection at 5 years. More trials are needed to control random errors and to reach conclusive evidences, but until date, resection is preferable to ablation for HCC of 2–3 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation